A view of clustering as emergent and innovative processes. Issue 4 (20th April 2020) - Johansen, Frode Ramstad; Kerndrup, Søren; Andersson, Gunnar; Rubach, Synnøve
ABSTRACT: The aim of government cluster programmes is to create clusters that strengthen businesses competitive edge and generate local development. Recent research, however, identifies missing elements regarding agency in existing path dependency explanations of the way in which clusters develop. In an alternative explanation, path creation emphases the distinction between agency and structure as 'flattened', and action-net emphases organising as an ongoing activity with only temporary stable implementations. This is explored in an analysis of a funded cluster project in the making, through varying and complex innovative processes, from 2006 until 2016. The findings show clustering as a path development process with knowledgeable actors mindfully framing opportunities and artefacts creating opportunities, and to be not as unambiguous and well-defined as expressed in traditional analyses, that have an outside perspective and focusing on structure and actors. Cluster projects and programmes potential lie in framework, tools and methods, more than in the financing.